Keragaman Genetik dan Hubungan Kekerabatan pada Tiga Jenis Aquilatria Menggunakan Penanda RAPD - AYPBC Widyatmoko; Elsih Dian Ariningsih; Aniek Prasetyaningsih (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2011)
Gaharu is an imprortant species of non wood forest product of Aquilaria spp with hight economic value. The natural stand has been exploited very intensive. The aim of the study were to investigate level of Aquilaria (namely A. malaccensis, a. beccariana and A. microcarpa) in order to provide genetic information for developing conservation strategy of the species. Aamples were colleted from 7 populations and analyzed using 26 RAPD primers. Total of 84 polymorpic loci have been obtained from these primers. Mean of genetic diversity within population indicated by A. malaccensis Muara Bungo population. A. malaccensis Berau population has the lowest genetic diversity. The highest genetic distance between populations was between A. micricarpa samboja and A. beccariana Berau. In contrast, genetic distance between A. Microcarpa Bearu and A. malaccensis Berau was the the lowest (0.017). based on Cluster analysis, The seven populations were divided into 2 groups. The first group consisted of 2 populations of A. malaccensis and A. microcarpa from Kalimantan.